Total Synthesis of a Reversed-Bacicyclin Using a Combination of Solid- and Solution-Phase Methods - Rani Maharani; Anastasya Firdausi; Tri Mayanti; Desi Harneti; Nurlelasari Nurlelasari; Safri Ishmayana; Kindi Farabi; Unang Supratman; Ace Tatang Hidayat (Indonesian Journal of Chemistry, 2022)
Bacicyclin is a cyclic hexapeptide with antibacterial activity against Enterococcus faecalis and Staphylococcus aureus with minimum inhibition concentration (MIC) values of 8 and 12 µM, respectively. Studies on a reversed sequence of bacicyclin were conducted to investigate how the reversed peptide sequence affects its biological properties. A reversed-bacicylin, cyclo-(Gly-Leu-Val-Ile-Ala-Phe), was successfully synthesized by constructing the linear precursor on 2-chlorotrityl chloride resin using a Fmoc-based strategy. The HATU/HOAt reagent was applied in all peptidic bond formations, and the desired linear hexapeptide (82% yield) was cleaved off the resin using a mixture of trifluoroacetic acid:dichloromethane (2:8). The linear peptide was cyclized using 1-[bis(dimethylamino)methylene]-1H-1,2,3-triazolo[4,5-b]pyridinium-3-oxidehexa-fluorophosphate (HATU) as a coupling agent and diisopropylethylamine (DIPEA) as the base in a very dilute solution (0.001 M) in dichloromethane, then purified by octadecyl silica gel (ODS) column chromatography to obtain the reversed-bacicyclin (43.7% yield). The purity of the cyclic product was analyzed using analytical RP-HPLC (tR = 20.01 min), and characterized by HR-TOF-MS, 1H-NMR, and 13C-NMR. The biological activity of the reversed-bacicyclin is much lower compared to bacicyclin, indicating that the amino acid sequence of the cyclopeptide dictates the antibacterial activity. This finding gives additional information on the relationship between peptide sequence and biological properties.